Potensi Bisnis Hotel sebagai Trend Staycation dalam Mendukung Pertumbuhan Sektor Pariwisata di Indonesia - Sesde Seharja; Giska Hitto; Andin Rusmini (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The Covid-19 pandemic affected many sectors, including the hospitality, the businesses of travel, food and drink, and entertainment services. Even the future of tourism is seen with pessimism, particularly in places where it is the main industry and where growth is planned. This may incentivize the travel and hospitality sector, particularly the hotel sector, to explore for strategies to weather the Covid-19 pandemic. This research uses a literature survey method. This method helps understand the relevance of new research and its relationship with previous research, identifying all previous scientific literature, including books, journal articles and theses, relating to the potential of the hotel business as a Staycation trend. This research aims to determine the potential of the hotel business as a Staycation trend. The research results show that 4-star and 3-star hotels differ in their understanding and application of the terms Daycation and Staycation, which mean a holiday of one day or a maximum of eight hours, however two out of five hotels still use the term Staycation even though the holiday is less than eight hours. During the pandemic, the term Staycation is also used. The findings indicate that it is important to maintain or improve hotel products and the use of digital marketing, especially social media, and continue to innovate to maintain a good image which relate to the prospects of the hotel business as a holiday style.